Self‐admission to inpatient treatment for patients with anorexia nervosa: The patient's perspective. Issue 4 (20th January 2017) - Strand, Mattias; Bulik, Cynthia M.; von Hausswolff‐Juhlin, Yvonne; Gustafsson, Sanna A.
Abstract: The aim of the present study was to explore patients' experiences of participating in a self‐admission program at a specialist eating disorders clinic. Sixteen adult program participants with a diagnosis of anorexia nervosa were interviewed at 6 months about their experiences in the self‐admission program. A qualitative content analysis approach was applied to identify recurring themes. Four themes were identified: Agency and Flexibility, Functions, Barriers, and Applicability. Participants used self‐admission to boost healthy behaviors, to prevent deterioration, to forestall the need for longer periods of hospitalizations, and to get a break from overwhelming demands. Quick access to brief admissions provides a safety net that can increase feelings of security in everyday life, even for patients who do not actually make use of the opportunity to self‐admit. It also provided relief to participants' relatives. Furthermore, participants experienced that self‐admission may foster agency and motivation. However, the model also requires a certain level of maturity and an encouraging environment to overcome barriers that could otherwise hinder optimal use, such as ambivalence in asking for help. Informants experienced that self‐admission could allow them to gain greater insight into their disease process, take greater responsibility for their recovery, and transform their health care from crisis‐driven to proactive. By offering a shift in perspective on help‐seeking and participation, self‐admission may potentially strengthen participants' internal responsibility for their treatment and promote partnership in treatment.